A study on customer satisfaction of facilities management & safety aspect in shopping mall / Nor Farah Atika Masjoni - Masjoni, Nor Farah Atika (Faculty Architecture, Planninng and Surveying, 2015)
The facilities management (FM) is an industry has coordinating all the efforts related to the planning, design and construction management including systems, equipment and furniture and to enhance the ability of organizations to compete in a rapidly changing world. The purpose this research is to study customer satisfaction on facilities management and safety aspect at shopping mall. Firstly, the focus of this research is to identify the customer satisfaction and need on the facilities management and safety aspect at the shopping mall. Secondly, to evaluate facilities management and safety aspect at shopping mall. Finally to recommend how to improve the facilities management and the safety aspect for customer at the shopping mall. The Three (3) shopping malls in Klang Valley are chosen AEON Bukit Tinggi Klang, Setia City Mall and Shah Alam Convention Center (SACC) mall. The methodology for are distributedquestionnaire to customer and informal interview to the customer and staff. Secondary data collected from article, journal, internet and observation. The findings are overall the findings of this study indicate that respondents are satisfied on the facilities management and safety aspect at shopping mall. This is because all facilities provided majority is in a good condition and easy to manage. Thus, from the analysis researcher can conclude the overall of the shopping mall provided the facilities and safety aspect were in good condition and easy to maintain. These is because the customer could adapt with the thing that are not provided and lastly the facilities and safety aspect provided to satisfaction were safe to use.